Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Chronological constraints on the tectonic evolution of the Chinese Tianshan Orogen through detrital zircons from modern and palaeo-river sands - Rong Ren; Shu-Wei Guan; Bao-Fu Han; Li Su (International Geology Review, 2017)

Characterization and Cu sorption properties of humic acid from the decomposition of rice straw - Yongbo Qi; Jun Zhu; Qingling Fu; Hongqing Hu; Xingmin Rong; Qiaoyun Huang (Environmental Science and Pollution Research, 2017)

Relationships between outgoing longwave radiation and diabatic heating in reanalyses - Kai Zhang; William J. Randel; Rong Fu (Climate Dynamics, 2017)

Changes in intermediate water conditions in the northern South China Sea using Globorotalia inflata over the last 20 ka - Yiping Yang; Rong Xiang; Jianguo Liu; Shaoying Fu; Liping Zhou; Shuhuan Du; Honghong Lü (Journal of Quaternary Science, 2017)
Intermediate circulation is one of the crucial controls of thermohaline changes in seawater. Due to the lack of data for some of the more significant indicators, there has been little research into past intermediate waters in the South China Sea (SCS). In particular, little is known of the thermohaline properties of intermediate water. Here, we present paired Mg/Ca and δ 18 O data for the planktonic foraminifera Globorotalia inflata from core GHE27L in the northern SCS; these data provide records of temperature and residual δ 18 O seawater (δ 18 O residual , being used as a proxy for salinity) to tentatively investigate changes in the intermediate water of the SCS over the last 20 ka. Our results show that G. inflata in the SCS grew principally within the 200–450 m water depth interval. Thermohaline changes recorded by G. inflata indicate warm and relatively freshening water during the Last Glacial Maximum (LGM, 20–17.7 ka BP ), changing to warm and saline waters between 17.7 and 13.6 ka BP . In general, waters during the 13.6–8.3 ka BP period were characterized by high temperatures and salinity, with obvious millennial‐scale fluctuations, after which, during the Holocene, they became cold and fresh. We suggest that the temperature and salinity of the intermediate water of the SCS recorded by G. inflata in core GHE27L were possibly associated with a switch in intermediate water masses. During the LGM, the intermediate water in the northern SCS was mainly impacted by North Pacific Intermediate Water (NPIW), but that subsequently the influence of Antarctic Intermediate Water strengthened during the last deglaciation and Pre‐Boreal period (17.7–8.3 ka BP ). After this period, NPIW was the principal control of the intermediate water of the SCS again.

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Tolerance and stress response of sclerotiogenic Aspergillus oryzae G15 to copper and lead - Dan-Dan Long; Rong-Rong Fu; Jian-Rong Han (Folia Microbiologica, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)